Endogamous Marriage Of Jamaah Tarbiyah: A Sociological Study Of The Jamaah Tarbiyah In Salatiga - Ilyya Muhsin (AHKAM : Jurnal Ilmu Syariah, 2017)
This article discusses the endogamous marriage of Jamaah Tarbiyah in Salatiga, Central Java based on a sociological perspective. The framework of Bourdiue theory, particularly capital and habitus concept, was applied to analyze the case. Jamaah Tarbiyah was able to force the cadre to get married in endogamous system based on ‘its own capital’. But, when the system was on process sometime it run in coercive way and there was a symbolic violence. As result, the coercive way raised a habitual action (habitus). The habitus resulted a doxa as well as a heterodoxa (counter doxa) when doxa opposed topersonal interest. Dialectic of the habitus, doxa, and hetrodoxa influenced on the member’s social life when endogamous marriage was practiced. DOI: 10.15408/ajis.v17i1.6226